2022
DOI: 10.3390/ma15238469
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Approach to the Hydrothermal Synthesis of Silica Nanoparticle/Carbon Nanostructure Luminescent Composites

Abstract: Luminescent carbon nanostructures (CNSs) have been intensively researched, but there is still no consensus on a fundamental understanding of their structure and properties that limits their potential applications. In this study, we developed a facile approach to the synthesis of luminescent composite SiO2 nanoparticles/CNSs by the targeted formation of a molecular fluorophore, as the significant luminescent component of CNSs, on the surface of a silica matrix during a one-stage hydrothermal synthesis. Silica n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…34,35 For the synthesis of IPCA temperature, processing time, and reagent ratio can be varied. 33,35,38,45 In our previous study it was found that during hydrothermal synthesis at 180 1C for 3 hours 37 and a ratio of CA to EDA of 1 : 1.5, 46 the molecular fluorophore IPCA is formed as the main product. In this regard, we used these conditions to obtain CeO 2 NPs modified by IPCA (CeO 2 -IPCA NPs).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 For the synthesis of IPCA temperature, processing time, and reagent ratio can be varied. 33,35,38,45 In our previous study it was found that during hydrothermal synthesis at 180 1C for 3 hours 37 and a ratio of CA to EDA of 1 : 1.5, 46 the molecular fluorophore IPCA is formed as the main product. In this regard, we used these conditions to obtain CeO 2 NPs modified by IPCA (CeO 2 -IPCA NPs).…”
Section: Resultsmentioning
confidence: 99%
“…It is known that IPCA obtained by the hydrothermal method from CA and EDA has a relatively high quantum yield of 460%. 32,37,46 CeO 2 -IPCA NPs obtained at a Ce 3+ to CA ratio of 1 : 3 have a QY of 62 AE 2%, comparable to the molecular fluorophore IPCA. Samples with other ratios are characterized by a lower QY (Table 1).…”
Section: Characterization Of Ceo 2 -Ipca Npsmentioning
confidence: 93%
See 1 more Smart Citation
“…The relative QY of QD emission was calculated as described in [ 31 ], relative to fluorescent dye Coumarin 153 (ethanol solution, peak optical density 0.1, QY 53%). The excitation and emission wavelengths of the QY measurement were 360 and 514 nm, respectively.…”
Section: Methodsmentioning
confidence: 99%